The effects of herbal medicine (Jujadokseo-hwan) on quality of life in patients with mild cognitive impairment: Cost-effectiveness analysis alongside randomized controlled trial - Ji-Eun Lee; Hyung Won Kang; Sun-A Jung; So-Young Lee; Ju Yeon Kim; Da Eun Lee; Jin-Hyung Jeong; In Chul Jung; Eun Cho (Integrative Medicine Research)
Background: Mild cognitive impairment (MCI), the early stage of dementia, requires effective intervention for symptom management and improving patients’ quality of life (QoL). Jujadokseo-hwan (JDH) is a Korean herbal medicine prescription used to improve MCI symptoms, such as memory deficit. This study evaluates the improvement in QoL through JDH. Alongside a clinical trial, it estimates the cost-effectiveness of JDH, compared to placebo, for MCI over 24 weeks. Methods: Changes in QoL were measured using the EuroQol-5 Dimensions (EQ-5D) and Korean version QoL-Alzheimer's Disease (KQOL-AD). Direct medical and non-medical costs were surveyed and incremental cost-effectiveness ratios (ICER) per QALY for JDH were produced. Results: In total, 64 patients were included in the economic evaluation (n = 35 in JDH, n = 29 in placebo). In the JDH group, EQ-5D and KQOL-AD improved by 0.020 (p = .318) and 3.40 (p = .011) over 24 weeks, respectively. In the placebo group, they increased by 0.001 (p=.920) and 1.07 (p=.130), respectively. The ICER was KRW 76,400,000 per QALY and KRW 108,000 per KQOL-AD for JDH, compared to the placebo group. Conclusion: JDH is not considered a cost-effective treatment option compared with placebo; however, it positively affects QoL improvement in patients with MCI.